Rheology properties of glucopyranoside stabilized oil-water emulsions: Effect of alkyl chain length and bulk concentration of the surfactant - Niraula, B.; King, T.C.; Chun, T.K.; Misran, M. (2004)
Effect of the alkyl chain length and concentration of the surfactant on Rheology properties of O/W emulsions stabilized with homologues series of glucopyranoside was studied. The Rheology properties in turn are being used to describe emulsion structure, emulsifying effect and emulsion stability. The emulsifying property was also explored through interfacial tension measurement. The homologues series of glucopyranoside possess identical polar head group structure, whereas the alkyl chain length varied from C 7 to C 10. The O/W emulsions were prepared by mixing 0.8 volume fractions of oil phase into a much smaller volume fraction of water phase; in this case 0.2 volume fractions of aqueous surfactant solution. Given energy input during emulsification and bulk surfactant concentration kept constant, the given oil to water mixing ratio would give high internal phase ratio concentrated O/W emulsions with dispersed phase volume fraction of â0.8, whereas the average size of the droplets was varied with the variation of both the alkyl length and the surfactant concentration. The average droplet size decreased with increasing both the length of the alkyl tail and the bulk concentration of the surfactant, so did interfacial free energy and cmc. As expected the Rheology properties of these emulsion samples depended strongly on average droplet size of the dispersed phase. The steady shear Rheology properties, such as shear viscosity, degree of shear thinning and Ï y enhanced with the decrease in average droplet size. This implies that not only the size of the emulsion droplets decreased with increasing both the length of the alkyl tail and bulk concentration of the surfactant, but also the emulsion and its storage stability were improved and enhanced with the increase in these two factors. Likewise, in the oscillatory shear mode the degree of viscoelasticity also depended on average droplet size. The fact that the Gâ²â«Gâ³, it is evident that the elastic property is dominant in these emulsions over viscous property. As expected the degree of elasticity enhanced with decreasing average droplet size of the dispersed phase. The Gâ²(Ï)â«Gâ³(Ï) at all measured Ï, but the Gâ²(Ï 2) function was found to be linear whereas the Gâ³(Ï) functions was independent, indicating that the oscillatory shear property of these emulsions can not be adequately described by Maxwell type viscoelastic model. Also, the fact that, Î´ of these emulsions was much smaller than 45Â° at all measured oscillatory Ï, it is evident that elastic property of these emulsions dominated their viscous property. Î´ of these emulsions decreased strongly with decreasing droplet size, further implying that the degree of elasticity of these emulsions enhanced and improved with decreasing average droplets size.